A Review of ICT Applications in Construction - Ehab J. Adwan; Ali Al-Soufi (Society of Visual Informatics, 2018)
In this review paper we compiled and demonstrated the trends and patterns of the research published on ICT Applications in the construction industry over the past two decades (1996-2016), through employing a five phases profiling methodology which generated an acceptable set of 68 out of 202 articles and papers indexed by Elsevierâ€™s Scopus database. This paper reviews the utmost academic ICT applications and proposals/ initiatives in the construction industry taking an advantage of a previously generated research journal on ICT Technologies and Construction Tasks. A resulting classification of 11 categories of ICT Applications as appeared in literature along with their corresponding authors and dates was provided and discussed.Â